Answer: -6
======================================================
Step-by-step explanation:
Plug in x = 1
f(x) = 17-x^2
f(1) = 17-1^2
f(1) = 17-1
f(1) = 16
Repeat for x = 5 to find that f(5) = -8
Now we'll use the formula below to find the average rate of change from x = a to x = b.
![m = (f(b)-f(a))/(b-a)\\\\m = (f(5)-f(1))/(5-1)\\\\m = (-8-16)/(4)\\\\m = (-24)/(4)\\\\m = -6\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/7suf40x4tbe2mn846tpll6qsrg707gcb4k.png)
The average rate of change is -6
The formula is basically the slope formula, more or less. So that's why I used 'm' to represent the average rate of change.
The average rate of change on the interval [1,5] is the same as finding the slope through the lines (1, 16) and (5, -8)